State of the art of research conducted on the use of active methodologies in training courses of the military police - Patricio Cassemiro de Souza , Mákio; Roldan Viana, Flávia (Seven Editora, 2023)
The National Curricular Matrix (MCN) deals with the promotion and valorization of professionals in the area of public security in the training actions offered by educational institutions involved in initial and continuing education. Thinking about the motivation, efficiency, well-being, and global health of this professional, MCN (2014) brings as urgent the need to implement methodologies that value his image as a subject of himself and recognize himself as a member of a historical institution capable of committing himself to his constitutional mission DOI: https://doi.org/10.56238/devopinterscie-178